The Feminist Film: An Analysis of the Feminist Narrative Form in the Films of Rakshane Bani-Etemad, Pouran Derakshande, and Manijeh Hekmat - Malekpour, Miniature (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: In this paper, the aim is to examine film form and narrative in relation to gender identity and the politics of representation. Drawing distinctions between these methods make it possible to identify how feminist frameworks are used to examine identity, aesthetics, and ideology through film culture. Approach/Methodology/Design: Thematic analysis, employing a feminist perspective. Three films were selected for conducting this type of analysis: Rakshane Bani-Etemad’s ‘Nargess’, Manijeh Hekmat’s ‘Women’s Prison’ and Pouran Derakshande’s ‘Hush! Girls Don’t Scream. Findings: By understanding the representation of women in Iranian Cinema and the cultural/traditional norms and values of the Iranian Society, I argue that the narrative form identifies feminist perspectives, which create an Iranian feminist cinema. Combining textual analysis with a greater concern for the audience-text relationship, and the rejection of the male gaze, these films recognize texts as shaped by the struggle to make meaning amongst institutions which shapes the filmic text from different components of the socio-historical context, and which creates a relationship between feminist film and cultural studies. Practical Implications: Iranian female directors have been adopting a feminist approach in their films’ narrative structure dating back to the reformist period of the 90s. Through the social/political context of female characters and the counter-cinematic development of agents, circumstances, and surroundings of the systems of patriarchy and oppression, women directors have been applying feminist narrative form to their work as evident in Rakshane Bani-Etemad’s ‘Nargess,’ Manijeh Hekmat’s ‘Women’s Prison’ and Pouran Derakshande’s ‘Hush! Girls Don’t Scream. Originality/value: This paper analyzes the principles of female desire through these selected films, the patriarchal dominance of societal oppression, the female condition, and the examination of violence in the traditions and attitudes related to women while looking at the representation of this violence and oppression in the Iranian Society.